2023
DOI: 10.3847/2041-8213/ad0387
|View full text |Cite
|
Sign up to set email alerts
|

GOALS-JWST: Small Neutral Grains and Enhanced 3.3 μm PAH Emission in the Seyfert Galaxy NGC 7469

Thomas S.-Y. 劭愉 Lai 賴,
Lee Armus,
Marina Bianchin
et al.

Abstract: We present James Webb Space Telescope (JWST) Near Infrared Spectrograph (NIRSpec) integral field spectroscopy of the nearby luminous infrared galaxy NGC 7469. We take advantage of the high spatial/spectral resolution and wavelength coverage of JWST/NIRSpec to study the 3.3 μm neutral polycyclic aromatic hydrocarbon (PAH) grain emission on ∼200 pc scales. A clear change in the average grain properties between the star-forming ring and the central AGN is found. Regions in the vicinity of the AGN, with [Ne iii]/[… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 90 publications
0
11
0
Order By: Relevance
“…Intriguingly, they too detect a much larger L(6.2 μm)/L(7.7 μm) near the nucleus analogous to the upturn in our ratio profile. In the same galaxy, Lai et al (2023) detected an enhancement in L(7.7 μm)/L (11.3 μm) near the nucleus, another short-to-long ratio. García-Bernete et al (2022b) also reports a larger relative L(6.2 μm)/L (7.7 μm) in the nucleus using the same observations.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Intriguingly, they too detect a much larger L(6.2 μm)/L(7.7 μm) near the nucleus analogous to the upturn in our ratio profile. In the same galaxy, Lai et al (2023) detected an enhancement in L(7.7 μm)/L (11.3 μm) near the nucleus, another short-to-long ratio. García-Bernete et al (2022b) also reports a larger relative L(6.2 μm)/L (7.7 μm) in the nucleus using the same observations.…”
Section: Discussionmentioning
confidence: 80%
“…Sales et al (2010), García-Bernete et al (2022a) saw similar suppression of both L(6.2 μm)/L(7.7 μm) and L(7.7 μm)/L(11.3 μm) in the Spitzer spectra for the nuclei of AGN hosts and noted that their results are consistent with the logic of the selective destruction by AGN hypothesis. Recently, Lai et al (2023) showed using JWST spectra that L(3.3 μm)/L(11.3 μm), a sensitive tracer of PAH size, is suppressed in the nucleus of the Seyfert galaxy NGC 7469 compared to other regions in the same galaxy. However, in a Spitzer study of 35 Seyfert galaxies, Diamond-Stanic & Rieke (2010) found significant suppression of L(7.7 μm)/L(11.3 μm) but not of L(6.2 μm)/L(7.7 μm), which is another tracer for PAH size.…”
Section: Pah Band Ratios In Agn Galaxiesmentioning
confidence: 99%
“…Only the lines with at least a 3σ detection in each extraction are included. The fluxes of the 3.3 μm PAH and aliphatic feature are part of our companion paper (Lai et al 2023), which discusses the dust grain distribution in NGC 7469 in detail.…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…Our final data cubes have a spatial resolution of 0 14 at 1.12 μm, as obtained from the FWHM of the O I 1.12 μm emission line image, allowing us to resolve structures down to ∼50 pc at this wavelength. The spatial resolution is poorer at longer wavelengths, as demonstrated by Lai et al (2023), who measure a spatial resolution of 0 19 for dust features at 3.3 μm.…”
Section: Data Reductionmentioning
confidence: 95%
“…PAHs are extraordinarily resilient, being observed in close proximity to active galactic nuclei (e.g., García-Bernete et al 2022). They are destroyed by shocks (Micelotta et al 2010a) or X-rays associated with luminous active galactic nuclei (Xie & Ho 2022;Lai et al 2023) and T Tauri stars (Siebenmorgen & Krügel 2010), however, and are rapidly destroyed in hot gas (e.g., Micelotta et al 2010b); therefore, they trace the cooler phases of the ISM and their spectrum provides key information on the physical conditions in those phases.…”
Section: Introductionmentioning
confidence: 99%